A starch-based edible composite film with biological activity and preparation method thereof
By predispersing and solubilizing curcumin with steviol and anhydrous ethanol in the starch film, and evenly dispersing it in the starch film liquid through solvent replacement technology, the problem of insufficient mechanical properties and barrier properties of the starch base film is solved, and the bioactivity and performance of the film is significantly improved, and a bioactive starch-based edible composite film suitable for food packaging is prepared.
Patent Information
- Application Number
- CN202211099594.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-07
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-09-07
AI Technical Summary
The existing starch-based film has defects in mechanical properties and barrier properties, and curcumin is unevenly dispersed in the aqueous starch film, which limits its biological activity.
Curcumin was predispersed and solubilized by steviol and anhydrous ethanol, and the solvent replacement technology was used to completely dissolve curcumin into aqueous starch film, inducing its recrystallization into needle-like microcrystals to improve dispersion and biological activity; at the same time, the polyhydroxy properties of steviol were used to enhance the mechanical properties and barrier properties of the film.
The dispersion uniformity and release of curcumin in the membrane are significantly improved, the mechanical properties and barrier properties of the membrane are improved, and the performance of multiple films is synchronized, and a bioactive starch-based edible composite film suitable for food packaging is prepared.
Smart Images

Figure CN116253908B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a starch-based edible composite film with biological activity and a preparation method thereof, and belongs to the field of food packaging. Background Art
[0002] Due to the increasing shortage of fossil resources, the increasing severity of "white pollution" and the gradual increase in environmental awareness, degradable packaging films made from renewable resources such as natural polymers are considered to be a type of green packaging material that can replace traditional plastic products, and have attracted widespread attention in the packaging field. Starch has the advantages of wide sources, degradability, and renewability. Its solution after heating and gelatinization can be formed into a film through a drying process, and has become a type of degradable food packaging film with good development prospects. At present, most starch-based films have defects such as poor mechanical properties, poor barrier properties (such as moisture and light blocking), and easy breeding of bacteria, which are greatly limited in practical application.
[0003] Curcumin (Curcumin, CUR) has been proven to be a safe, non-toxic and natural polyphenolic compound with a variety of biologically active functions, which can be used as a food additive for the coloring and flavoring of food. In addition, its antibacterial, antioxidant and pH responsiveness have been widely used to develop active films (CN201710024265.9) and smart films (CN201610620161.X). Although the introduction of hydrophobic curcumin can reduce the water sensitivity of starch film, it also shows extremely low water solubility, resulting in uneven dispersion in aqueous starch film liquid, and limiting the performance of its biological activity (Food Chemistry 2022, 371, 131121). Therefore, seeking a cheap, simple and effective film preparation process that can improve the dispersibility and biological activity of curcumin in starch film liquid is of great value to the development of bioactive starch film.
[0004] Stevioside (STE) is the main strong sweet ingredient extracted from the plant stevia. The stevioside molecule consists of a hydrophobic steviol central skeleton and hydrophilic glycosyl groups containing polyhydroxy groups on both sides, showing a typical Bola-type amphiphilic structure. This structure is similar to a surfactant and can be used to increase the solubility of fat-soluble substances (phloretin) in aqueous systems (CN201910948738.3). It also has the potential to regulate the physical and chemical properties of polysaccharide membranes as a polyhydroxy compound.
[0005] In summary, the introduction of stevioside is a potential strategy to simultaneously improve the water solubility of curcumin and the performance of starch films. However, there is currently no technical route to improve the dispersibility and biological activity of curcumin in films using stevioside, and there is no report on its use in improving the performance of starch films. Summary of the invention
[0006] [Technical issues]
[0007] Although pure starch film and curcumin-containing starch film can be used as green food packaging materials, they still have the defects of poor mechanical properties and poor barrier properties (such as moisture and light blocking). At the same time, the low water solubility of curcumin makes it difficult to disperse evenly in the aqueous starch film liquid and its biological activity is hindered. These defects limit the application of curcumin-containing starch film in food packaging.
[0008] [Technical solution]
[0009] In order to solve the above problems, the present invention uses stevioside and anhydrous ethanol to pre-disperse and solubilize curcumin, and through the solvent replacement of "organic phase-mixed phase-aqueous phase", the curcumin is completely dissolved in the aqueous starch film liquid, thereby inducing the curcumin to recrystallize into needle-shaped micron crystals during the film-forming process and uniformly disperse in the film, thereby promoting its biological activity; at the same time, the mechanical properties and barrier properties of the starch film are improved by utilizing the polyhydroxy characteristics of stevioside; thereby achieving the purpose of simultaneously improving multiple film properties, and realizing a starch-based edible composite film with biological activity that can be used for food packaging.
[0010] The first object of the present invention is to provide a method for preparing a starch-based edible composite film having biological activity, comprising the steps of:
[0011] (1) Pre-dispersion and solubilization treatment:
[0012] Pre-dispersing and solubilizing stevioside and curcumin in anhydrous ethanol to prepare an active ingredient organic phase stock solution;
[0013] (2) Solvent replacement:
[0014] Add water to the organic phase stock solution of the active substance obtained in step (1) to dilute it, heat, ventilate and stir until the ethanol is completely volatilized, complete the replacement process from "organic phase" to "mixed phase" and then to "aqueous phase", and obtain the aqueous phase stock solution of the active substance;
[0015] (3) Hydrothermal Gelatinization:
[0016] Adding starch and glycerol to the aqueous phase stock solution of active substances obtained in step (2), and heating the solution to obtain a composite membrane slurry;
[0017] (4) Casting film:
[0018] The composite film slurry obtained in step (3) is cast into a film, cooled and dried to obtain the starch-based edible composite film with biological activity.
[0019] In one embodiment of the present invention, the mass ratio of stevioside to curcumin in step (1) is 1:0.01-0.14.
[0020] In one embodiment of the present invention, the amount of anhydrous ethanol in step (1) is equal in volume to the mixture of stevioside and curcumin.
[0021] In one embodiment of the present invention, the dilution in step (2) is such that the concentration of stevioside relative to water is 0.0025-0.0125 g / mL.
[0022] In one embodiment of the present invention, the heating, ventilation and stirring in step (2) are specifically: the heating temperature is 25-90° C.; the ventilation wind speed is 0.4-0.5 m / s; and the stirring rate is 500-800 rpm.
[0023] In one embodiment of the present invention, the starch described in step (3) includes one or more of cassava starch, common corn starch, waxy corn starch, rice starch, wheat starch, and potato starch, and its concentration relative to water is 3.0 to 5.0 wt%.
[0024] In one embodiment of the present invention, the amount of glycerol added in step (3) is 0.3-0.4 g / g starch.
[0025] In one embodiment of the present invention, the heating treatment in step (3) is performed at 80-100° C. for 30-45 min.
[0026] In one embodiment of the present invention, the film casting described in step (3) is to spread the composite film slurry flat in a mold to form a film, and the amount of the film casting is 0.01 to 0.015 g / cm based on the dry weight of starch. 2 .
[0027] In one embodiment of the present invention, the cooling and drying temperatures in step (3) are both 40-45°C.
[0028] In one embodiment of the present invention, after the drying in step (3), moisture balance is required, and the relative humidity of the moisture balance environment is 50-75%; the time for drying and moisture balance of the composite film is until the weight is constant.
[0029] The second object of the present invention is a starch-based edible composite film with biological activity prepared by the method of the present invention.
[0030] The third object of the present invention is to use the bioactive starch-based edible composite film of the present invention in the field of packaging films.
[0031] In one embodiment of the present invention, the packaging film field includes the field of food packaging films, specifically including edible, biodegradable or bioactive food packaging films.
[0032] A fourth object of the present invention is to provide a food packaging film, which uses the bioactive starch-based edible composite film of the present invention.
[0033] The fifth object of the present invention is to provide a method for simultaneously improving the antibacterial activity, pH responsiveness and bioactive release rate of starch film, wherein the method comprises adding stevioside and curcumin to the starch film, and specifically comprises the following steps:
[0034] (1) Pre-dispersion and solubilization treatment:
[0035] Pre-dispersing and solubilizing stevioside and curcumin in anhydrous ethanol to prepare an active ingredient organic phase stock solution;
[0036] (2) Solvent replacement:
[0037] Add water to the organic phase stock solution of the active substance obtained in step (1) to dilute it, heat, ventilate and stir until the ethanol is completely volatilized, complete the replacement process from "organic phase" to "mixed phase" and then to "aqueous phase", and obtain the aqueous phase stock solution of the active substance;
[0038] (3) Hydrothermal Gelatinization:
[0039] Adding starch and glycerol to the aqueous phase stock solution of active substances obtained in step (2), and heating the solution to obtain a composite membrane slurry;
[0040] (4) Casting film:
[0041] The composite film slurry obtained in step (3) is cast into a film, cooled and dried to obtain a starch-based edible composite film with biological activity.
[0042] [Beneficial Effects]
[0043] (1) The materials used in the present invention are all food raw materials that are widely available, low-priced, compliant and non-toxic. The produced film materials are green, environmentally friendly, safe and edible, which improves the comprehensive utilization rate of food raw materials and creates good social and economic benefits.
[0044] (2) The present invention uses stevioside and anhydrous ethanol to pre-disperse and solubilize curcumin, and through the solvent replacement of "organic phase-mixed phase-aqueous phase", significantly improves the solubility of hydrophobic curcumin in aqueous starch film liquid, induces its recrystallization into needle-shaped micron crystals during the film formation process, improves the dispersion uniformity of curcumin in the film, and enhances the release of curcumin from the film (the in vitro release rate in an aqueous environment is increased by 4.9 times).
[0045] (3) The present invention utilizes the polyhydroxyl characteristics of stevioside to significantly improve the mechanical properties and barrier properties of the film, which are mainly manifested in that: with the introduction of stevioside, the elongation at break of the film is increased from about 50% to about 85%, the toughness is increased from 1.64 to 2.26 MJ / m3, and the water vapor transmission rate is reduced from 3.05 to 2.13 (×10 -10 g / ms Pa), the UV transmittance is completely reduced to 0%.
[0046] (4) Compared with pure starch film and starch film containing only curcumin, the starch-based biocomposite film prepared by the present invention has better antibacterial activity and more sensitive pH responsiveness, and can be applied to the production of active or intelligent packaging films with lower cost and simple process.
[0047] (5) The starch-based edible composite film of the present invention has biological activity, which improves the release of curcumin from the starch film, so that it can better exert biological activities such as inhibiting enzyme activity and controlling blood sugar when consumed; it also enhances the pH response sensitivity and antibacterial activity of the starch film, which is more conducive to monitoring and maintaining the freshness of food when used as packaging. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a photograph of the appearance of the bioactive starch-based edible composite film prepared in Example 1.
[0049] Figure 2 The microscopic observation diagram (a) shows the dispersion state of curcumin in the bioactive starch-based edible composite film prepared in Example 1 and (b) shows the crystal morphology.
[0050] Figure 3 The absorbance and appearance of the aqueous phase stock solutions of active ingredients containing different stevioside / curcumin mass ratios prepared in Example 2.
[0051] Figure 4 The diameter shrinkage rate and appearance of the composite films containing different stevioside concentrations prepared in Example 3.
[0052] Figure 5 The diagram is a microscopic observation diagram of the curcumin dispersion state (a) and the crystal morphology (b) inside the starch film containing only curcumin obtained in Comparative Example 2.
[0053] Figure 6 The light transmittance of the film samples prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3.
[0054] Figure 7 The antibacterial effects of the film samples prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown.
[0055] Figure 8It is the cumulative release rate of the film samples prepared in Example 4 and Comparative Example 2.
[0056] Fig. 9 The food monitoring sensitivity of the film samples prepared in Example 4 and Comparative Example 2.
[0057] Fig.10 The microscopic observation diagram (a) of the dispersion state of curcumin inside the composite film prepared in Comparative Example 4 and (b) the crystal morphology. DETAILED DESCRIPTION
[0058] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0059] Test method:
[0060] 1. Observation of the dispersion and crystal morphology of curcumin
[0061] The dispersion and crystal morphology of curcumin inside the membrane were observed using a LV200N VMR-3020 microscope (Nikon, Japan).
[0062] 2. Determination of light transmittance
[0063] A TU-1900 UV-visible spectrophotometer (Puxi, China) was used in transmission mode to scan the spectrum in the range of 200 to 800 nm.
[0064] 3. Determination of mechanical properties
[0065] The mechanical properties of the film samples were analyzed using a TA.XT2i texture analyzer (Stable Microsystems, UK) with a tension clamp probe A / TG. The tensile strength (MPa), elongation at break (in%), toughness (MJ / m 3 ) and Young’s modulus (MPa).
[0066] 4. Determination of water vapor transmission rate
[0067] Under the conditions of 75% relative humidity and 20°C, an acrylic permeation cell containing anhydrous silica gel was used, and the top was sealed with a membrane sample. The weight of the permeation cell was weighed at regular intervals to determine the water vapor permeability (WVP) by the gravimetric method. The calculation formula of WVP is as follows:
[0068] WVP (g / ms Pa) = (Slope×l×100) / (S×△P) (1)
[0069] Where Slope is the linear regression slope of the weight loss versus time curve, S is the exposed area of the membrane in the permeation cell, l is the average thickness of the membrane measured by a micrometer (m, with an accuracy of 0.001 mm), and △Ps (Pa) is the partial pressure difference of water vapor passing through the membrane (here 1753.55 Pa).
[0070] 5. In vitro release test:
[0071] An appropriate amount of about 1g of the composite film was placed in a conical flask filled with pH 7.4 phosphate buffer and continuously shaken in a water bath shaker at 37°C and 120rpm. At predetermined time intervals (0.25, 0.5, 1, 2, 4, 6, 8, 10, 12, 18, 24, 30, 36h), 1mL aliquots were taken out, and the taken out volume was replaced with fresh buffer. The taken out aliquots were scanned for absorbance (300-550nm) under a UV spectrophotometer, and the peak value was selected to compare with the standard curve to calculate the release rate.
[0072] 6. Antibacterial performance test:
[0073] The Escherichia coli and Staphylococcus aureus used represent Gram-negative and Gram-positive bacteria, respectively. The membrane was cut into 1-cm-diameter discs and placed in direct contact with an agar plate inoculated with the corresponding bacterial inoculum (10 4 CFU / ml), incubated at 37°C, and the bacteria were visually observed and the inhibition zones were calculated after 24 h.
[0074] 7. Test of pH response sensitivity for food freshness monitoring:
[0075] One shrimp was sealed in a sterile culture dish, the membrane sample was attached to the lid of the culture dish, and stored in an incubator (25° C., relative humidity 75%) for 72 hours, and the changes in membrane color over storage time were recorded by taking photos.
[0076] Example 1
[0077] A method for preparing a starch-based edible composite film having biological activity comprises the following steps:
[0078] (1) Pre-dispersion and solubilization treatment:
[0079] Stevioside and curcumin were dispersed in an equal volume of anhydrous ethanol at a mass ratio of 1:0.14 for pre-dispersion and solubilization to prepare an organic phase stock solution of the active ingredient;
[0080] (2) Solvent replacement:
[0081] Add distilled water to the active substance organic phase stock solution prepared in step (1) to dilute it to a stevioside concentration of 0.0125 g / mL (relative to the concentration of water), and completely volatilize the anhydrous ethanol at 50° C., 800 rpm stirring speed and 0.5 m / s ventilation speed to complete the replacement process from "organic phase" to "mixed phase" and then to "aqueous phase", thereby preparing an active substance aqueous phase stock solution;
[0082] (3) Hydrothermal Gelatinization:
[0083] Add 4 wt % cassava starch and 0.4 g / g starch of glycerol to the active substance aqueous phase stock solution prepared in step (2), and heat at 95° C. for 40 minutes to prepare a composite membrane slurry;
[0084] (4) Casting film:
[0085] The composite membrane slurry prepared in step (3) is heated to 0.01-0.015 g / cm 2 The starch dry basis weight is spread flat in a mold, cooled to 40° C. and dried at this temperature. The composite film dried to constant weight needs to balance the moisture in a relative humidity of 70%. The film is removed after the moisture balance reaches a constant weight, thereby obtaining the starch-based edible composite film (CUR-STE@SF) with biological activity.
[0086] The obtained bioactive starch-based edible composite film was subjected to performance tests, and the test results are as follows:
[0087] Figure 1 This is a photo of the appearance of the bioactive starch-based edible composite film. Figure 1 It can be seen that the starch-based edible composite film is completely formed and has uniform color without obvious cracks and wrinkles.
[0088] Figure 2 This is a microscopic observation of the dispersion state and crystal morphology of curcumin in the bioactive starch-based edible composite film. Figure 2 It can be seen that curcumin is uniformly dispersed inside the composite film in the form of needle-shaped micron-sized crystals.
[0089] Example 2 Different stevioside and curcumin mass ratios
[0090] The mass ratio of stevioside to curcumin in step (1) of Example 1 was adjusted to 1: 0.18, 0.16, 0.12, 0.10, 0.08, 0.06, 0.04, 0.02; the rest was kept consistent with Example 1 to obtain starch-based edible composite films containing different stevioside / curcumin mass ratios.
[0091] The obtained starch-based edible composite films containing different stevioside / curcumin mass ratios were subjected to performance tests. The test results are as follows: Figure 3 :
[0092] from Figure 3 It can be seen that: when the stevioside / curcumin mass ratio is lower than 1:0.14 (i.e., 1:0.16 and 1:0.18), the measured absorbance is lower than the theoretical absorbance, and the aqueous stock solution becomes obviously turbid, indicating that the amount of curcumin added exceeds the solubilization capacity of the pre-dispersed system based on stevioside / anhydrous ethanol, and is not suitable for the preparation of starch-based edible composite films with biological activity; the measured absorbance of the aqueous stock solution with a stevioside / curcumin mass ratio higher than 1:0.14 is close to the theoretical value, and the appearance is clear and transparent, indicating that curcumin is completely solubilized in the aqueous system, and is suitable for the preparation of starch-based edible composite films with biological activity; the film samples prepared from the active substance aqueous stock solution containing a stevioside / curcumin mass ratio in the range of 1:0.02 to 0.14 all have a complete shape and uniform coloring, without obvious cracks and wrinkles.
[0093] Example 3 Different stevioside concentrations
[0094] The step (2) of Example 1 was adjusted by adding distilled water to dilute the stevioside concentration to 0.0025, 0.0050, 0.0075, 0.0100, 0.0250, 0.0375, and 0.0500 g / mL (relative to the concentration of water), and the rest was consistent with Example 1 to obtain starch-based edible composite films with different stevioside concentrations.
[0095] The obtained starch-based edible composite films with different stevioside concentrations were subjected to performance tests. The test results are as follows: Figure 4 :
[0096] from Figure 4 It can be seen that the active material stock solutions with different stevioside concentrations can be used to prepare composite films, but when the stevioside concentration is higher than 0.0250 g / mL, the composite film shows obvious diameter shrinkage, which is not suitable for the preparation of starch-based edible composite films with biological activity; when the stevioside concentration is lower than 0.0125 g / mL, the composite film does not shrink in diameter or only shrinks insignificantly, which is suitable for the preparation of starch-based edible composite films with biological activity.
[0097] Comparative Example 1 Pure starch film (SF)
[0098] A method for preparing pure starch film comprises the following steps:
[0099] (1) Hydrothermal gelatinization:
[0100] Add 4 wt% cassava starch and 0.4 g / g glycerol to water, and heat at 95° C. for 40 minutes to prepare a membrane slurry;
[0101] (2) Cast film:
[0102] The membrane slurry was heated at 0.01-0.015 g / cm 2 The starch dry basis weight is spread flat in a mold, cooled to 40° C. and dried at this temperature. The composite film dried to constant weight needs to balance the moisture in a relative humidity of 70%. After the moisture balance reaches constant weight, the film is removed to obtain the pure starch film (SF).
[0103] Comparative Example 2 Starch film containing only curcumin (CUR@SF)
[0104] The stevioside in Example 1 was omitted, and the amount of curcumin and other operations were kept consistent with Example 1 to obtain the starch film containing only curcumin (CUR@SF).
[0105] Microscopic observation of the internal curcumin dispersion and crystal morphology of the starch film containing only curcumin (CUR@SF) Figure 5 ,from Figure 5 It can be seen that curcumin is non-uniformly dispersed inside the composite film in the form of relatively large micron-sized particle aggregates.
[0106] Comparative Example 3 Starch film containing only stevioside (STE@SF)
[0107] The curcumin in Example 1 was omitted, and the amount of stevioside and other operations were kept consistent with those in Example 1 to obtain the starch film containing only stevioside (STE@SF).
[0108] The films obtained in Example 1 and Comparative Examples 1, 2, and 3 were subjected to performance tests, and the test results are as follows:
[0109] Figure 6 is the light transmittance of the film, Figure 6 It can be seen that the transmittance of the composite film of Example 1 in the ultraviolet light region, which has the greatest impact on the shelf life of food, is almost 0%, which plays a role in complete ultraviolet light blocking, and the transmittance in the visible light region and the near-infrared light region is also reduced to below 20%; the pure starch film of Comparative Example 1 has a higher transmittance in the ultraviolet light region, and the transmittance in the visible light region and the near-infrared light region is as high as more than 40%; the composite film of Comparative Example 2 still has a certain transmittance in the ultraviolet light region, and the transmittance in the visible light region and the near-infrared light region is as high as nearly 30%; the composite film of Comparative Example 3 has a higher transmittance in the ultraviolet light region, and the transmittance in the visible light region and the near-infrared light region is as high as nearly 40%.
[0110] Figure 7 The antibacterial performance test results are as follows: Figure 7It can be seen that: after 24 hours of cultivation, no bacteria grew on the surface of the composite membrane of Example 1, and an inhibition zone appeared along the edge, which showed a good antibacterial effect; after 24 hours of cultivation, bacteria grew on the surface of the pure starch film of Comparative Example 1, and no inhibition zone appeared, so it had no antibacterial effect; after 24 hours of cultivation, no bacteria grew on the surface of the composite membrane of Comparative Example 2, but no inhibition zone appeared, and it only showed a contact antibacterial effect; after 24 hours of cultivation, bacteria grew on the surface of the composite membrane of Comparative Example 3, and no inhibition zone appeared, so it had no antibacterial effect.
[0111] Table 1 shows the test results of mechanical properties and water vapor barrier properties. It can be seen from Table 1 that the tensile strength and Young's modulus of the pure starch film of Comparative Example 1 are only slightly greater than those of the composite film prepared in Example 1, but the latter has significantly higher elongation at break and toughness than the former; the tensile strength and Young's modulus of the starch film containing only curcumin of Comparative Example 2 are slightly greater than those of the composite film, but the latter has significantly higher elongation at break and toughness than the former; the mechanical properties of the starch film containing only stevioside of Comparative Example 3 are similar to those of the composite film prepared in Example 1, but the former shows a UV / water vapor barrier effect that is significantly lower than that of the latter.
[0112] Table 1
[0113]
[0114] Figure 8 is the cumulative release rate of the films of Example 1 and Comparative Example 2, from Figure 8 It can be seen that the release rate of the composite film of Example 1 after 36 hours can reach 2.28%, indicating that it can better exert biological activities such as inhibiting enzyme activity and controlling blood sugar when consumed; the release rate of the composite film of Comparative Example 2 after 36 hours is only 0.45%, which is much lower than the release rate of the composite film prepared in Example 1.
[0115] Fig. 9 The food monitoring sensitivity of the membranes of Example 1 and Comparative Example 2 is as follows: Fig. 9 It can be seen that as the storage time of the composite film of Example 1 increases, the shrimp becomes corrupted from fresh, releasing volatile amino nitrogen, and the color of the composite film gradually changes from yellow to dark red, and a response change visible to the naked eye occurs; the color of the starch film containing only curcumin in Comparative Example 2 only slightly changes from yellow to reddish yellow, and it is difficult to distinguish its color change with the naked eye.
[0116] Comparative Example 4: Solvent-free replacement
[0117] A method for preparing a starch-based composite film comprises the following steps:
[0118] (1) Aqueous dispersion:
[0119] According to the mass ratio, addition amount and water dilution ratio of curcumin / stevioside in Example 1, curcumin and stevioside are directly dispersed and diluted with water to prepare an active substance aqueous phase stock solution;
[0120] (2) Hydrothermal gelatinization:
[0121] Adding 4 wt % cassava starch and 0.4 g / g glycerol to the active substance aqueous phase stock solution prepared in step (1), and heating at 95° C. for 40 minutes to prepare a composite membrane slurry;
[0122] (3) Casting film:
[0123] The membrane slurry prepared in step (2) is heated to 0.01-0.015 g / cm 2 The starch dry basis weight is spread flat in a mold, cooled to 40° C. and dried at this temperature. The composite film dried to constant weight needs to balance the moisture in a relative humidity of 70%. The film is removed after the moisture balance reaches constant weight to obtain the solvent-free replacement composite film.
[0124] During the experiment, it was found that the active ingredient aqueous stock solution in step (1) was obviously turbid due to undissolved curcumin.
[0125] The performance of the composite membrane without solvent replacement was tested. The test results are as follows Fig.10 :
[0126] Fig.10 The dispersion and crystal form of curcumin in the composite film. Fig.10 It can be seen that curcumin is non-uniformly dispersed in the composite film in the form of micron-scale particle aggregation; although the dispersion uniformity and crystal morphology are slightly better than those of the starch film containing only curcumin prepared in Comparative Example 2, it is still far inferior to the starch-based edible composite film with biological activity prepared in Example 1, indicating that the anhydrous ethanol dispersion step plays an important role in inducing recrystallization and uniform dispersion of curcumin.
[0127] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a starch-based edible composite film having biological activity, characterized in that: The steps include: (1) Pre-dispersion and solubilization treatment: Pre-dispersing and solubilizing stevioside and curcumin in anhydrous ethanol to prepare an active organic phase stock solution; the mass ratio of stevioside to curcumin is 1:0.01-0.14; (2) Solvent replacement: Add water to the active substance organic phase stock solution prepared in step (1) to dilute it, heat, ventilate and stir until the ethanol is completely volatilized, complete the replacement process from "organic phase" to "mixed phase" and then to "aqueous phase", and prepare the active substance aqueous phase stock solution; the dilution is such that the concentration of stevioside relative to water is 0.0025-0.0125 g / mL; (3) Hydrothermal gelatinization: Add starch and glycerol to the aqueous phase stock solution of active ingredients obtained in step (2), and heat the solution to obtain a composite film slurry; the concentration of starch relative to water is 3.0-5.0 wt %; and the amount of glycerol added is 0.3-0.4 g / g starch; (4) Cast film: The composite film slurry obtained in step (3) is cast into a film, cooled and dried to obtain the starch-based edible composite film with biological activity.
2. The method according to claim 1, characterized in that The amount of anhydrous ethanol used in step (1) is equal in volume to the mixture of stevioside and curcumin.
3. The method according to claim 1, characterized in that The starch in step (3) includes one or more of cassava starch, ordinary corn starch, waxy corn starch, rice starch, wheat starch, and potato starch.
4. The method according to claim 1, characterized in that: The heating treatment in step (3) is performed at 80-100° C. for 30-45 minutes.
5. The method according to claim 1, characterized in that The amount of the composite film slurry cast film in step (4) is 0.01 to 0.015 g / cm based on the dry weight of starch. 2 .
6. A starch-based edible composite film with biological activity prepared by the method according to any one of claims 1 to 5.
7. Use of the bioactive starch-based edible composite film according to claim 6 in the field of packaging films.
8. A food packaging film, characterized in that: The bioactive starch-based edible composite film according to claim 6 is used.
9. A method for simultaneously improving the antibacterial activity, pH responsiveness and bioactive release rate of starch films, characterized in that: The method adds stevioside and curcumin to the starch film, and specifically comprises the following steps: (1) Pre-dispersion and solubilization treatment: Pre-dispersing and solubilizing stevioside and curcumin in anhydrous ethanol to prepare an active organic phase stock solution; the mass ratio of stevioside to curcumin is 1:0.01-0.14; (2) Solvent replacement: Add water to the active substance organic phase stock solution prepared in step (1) to dilute it, heat, ventilate and stir until the ethanol is completely volatilized, complete the replacement process from "organic phase" to "mixed phase" and then to "aqueous phase", and prepare the active substance aqueous phase stock solution; the dilution is such that the concentration of stevioside relative to water is 0.0025-0.0125 g / mL; (3) Hydrothermal gelatinization: Add starch and glycerol to the aqueous phase stock solution of active ingredients obtained in step (2), and heat the solution to obtain a composite film slurry; the concentration of starch relative to water is 3.0-5.0 wt %; and the amount of glycerol added is 0.3-0.4 g / g starch; (4) Cast film: The composite film slurry obtained in step (3) is cast into a film, cooled and dried to obtain a starch-based edible composite film with biological activity.
Citation Information
Patent Citations
A method for preparing a curcumin / PVA / tara gum NH3 smart responsive membrane
CN106117577B
Edible fish skin collagen active composite membrane and preparation method thereof
CN106751925A
Phloretin solubilizing solid dispersion adopting stevioside as carrier and preparation method of phloretin solubilizing solid dispersion
CN110538145A
Potato starch-based degradable antibacterial packaging film and preparation method thereof
CN104448399A
Antibacterial and antioxidant edible gelatin composite membrane and preparation method thereof
CN107011683A